The Influence of Qira'at Sahih and Shadhdhah in the Interpretation of the Qur'an (Analysis of Surah Saba’ 19 in Tafsir al-Bahr al-Muhit) - Faiqoh Naufalia Arrozi; Lukman Hakim (al-Afkar, Journal For Islamic Studies, 2024)
The Qur'ān, as a guide for mankind, has been the object of continuous study from classical times to modern times today, involving various aspects including the history of its revelation, the history of its bookkeeping, its interpretation, its meaning content, its grammatical aspects, to the way of reading qira'at. Differences in qiraat have various impacts on the interpretation of the Qur'an, both in terms of changing the meaning and in terms that do not have a direct impact on interpretation, such as differences in dialect. This article examines the influence of saheeh and shadhdhah qiraat on the interpretation of verse 19 of Surah Saba' in Abu Hayyan's tafsir al-Bahr al-Muhit}. This study uses the method of literature (library research) with the aim of analyzing the influence of qiraat, both considered shahih and shadhdhah, on tafsir al-Bahr al-Muhit on verse 19 of Surah Saba'. The results showed that there is a significant influence of qiraat shahih and shadhdhah on the verse in tafsir al-Bahr al-Muhit. Qiraat shahih tends to provide clearer clarification of the meaning, while qiraat shadhdhah has the potential to change the meaning of the verse.